Capturing the Heritage of British Colonial School Building Through Measured Drawings in Malaysia: A Case of PULAPOL Batu Lama School - Abdul Rahim, Asiah; Aripin, Srazali; Sapian, Abdul Razak; Zubir, Hazwan (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2022)
This research is to convey the analytical studies of the Pusat Latihan Polis (PULAPOL) Batu Lama School. This research aims to present detailed information of the endogenous influences, particularly during the British colonization era. PULAPOL was the first Police Training Centre in Malaysia. It is located at Jalan Sultan Yahya Petra, Kuala Lumpur. It was constructed in 1938. The structural system used for the school’s construction was load-bearing brick masonry. The objectives of the studies are to: a) Increase the understanding and appreciation of Architectural Heritage of the Muslim World, b) Learn the techniques of measured drawings of heritage buildings with the emphasis on the building construction, detailing, research and documentation of the historical aspects of the building and its development, c) Appreciate the total concept and richness of the architectural heritage as well as to be able to value the environment and to understand the socio-economic-cultural way of life of local inhabitants. In general, the methodology adopted for the study is divided into pre-fieldwork, fieldwork and post-fieldwork. Data collected from interviews, case studies, observations, and measurements of the building. The data obtained from various methods are documented in reports and measured drawing. In conclusion, these research findings provide the chronology and history of the PULAPOL Batu Lama School that is rich in its historical values, materials used, construction techniques and passive design techniques.